Doing the Simple Tasks - Jones, Susie Williams (Tufts Archival Research Center, 2006)
Susie Jones believes spiritual fulfillment comes from attending to the mundane chores of daily life and describes her belief in the fundamental goodness of people her desrie to be one with God.